2008
DOI: 10.1086/523639
|View full text |Cite
|
Sign up to set email alerts
|

The DEEP2 Galaxy Redshift Survey: Color and Luminosity Dependence of Galaxy Clustering at \documentclass{aastex} \usepackage{amsbsy} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{bm} \usepackage{mathrsfs} \usepackage{pifont} \usepackage{stmaryrd} \usepackage{textcomp} \usepackage{portland,xspace} \usepackage{amsmath,amsxtra} \usepackage[OT2,OT1]{fontenc} \newcommand\cyr{ \renewcommand\rmdefault{wncyr} \renewcommand\sfdefault{wncyss} \renewcommand\encodingdefault{OT2} \normalfont \selectfont} \Decl

Abstract: We present measurements of the color and luminosity dependence of galaxy clustering at z $ 1 in the DEEP2 Galaxy Redshift Survey. Using volume-limited subsamples in bins of both color and luminosity, we find the following: (1) The clustering dependence is much stronger with color than with luminosity and is as strong with color at z $ 1 as is found locally. We find no dependence of the clustering amplitude on color for galaxies on the red sequence, but a significant dependence on color for galaxies within the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

38
145
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 215 publications
(185 citation statements)
references
References 104 publications
38
145
0
2
Order By: Relevance
“…These studies highlight a number of discrepancies between model predictions and observations. In particular, Coil et al (2008) show that red model galaxies are more strongly clustered than observed at z 1, particularly on small scales. Blue galaxies in the model show instead a lower clustering strength than observed, suggesting a significant deficit of blue satellite galaxies in the semi-analytical model of Croton et al (2006).…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations
“…These studies highlight a number of discrepancies between model predictions and observations. In particular, Coil et al (2008) show that red model galaxies are more strongly clustered than observed at z 1, particularly on small scales. Blue galaxies in the model show instead a lower clustering strength than observed, suggesting a significant deficit of blue satellite galaxies in the semi-analytical model of Croton et al (2006).…”
Section: Introductionmentioning
confidence: 76%
“…Here, the very prominent 1-halo term may be due to an overabundance of red satellite galaxies. Similarly, Coil et al (2008) find an absence of "Finger of God" (FoG, Jackson 1972) in the correlation function of blue model galaxies at z 1 at variance with red model galaxies, which have a very strong FoG. The FoG effect is associated with the infall of satellite galaxies inside haloes and its strength is related to the abundance of satellite galaxies (e.g.…”
Section: Colour-dependent Galaxy Clusteringmentioning
confidence: 89%
See 1 more Smart Citation
“…Figure 39: Auto-correlation length r 0 of DSFGs compared to a variety of galaxy populations over the redshift interval 0 < z < 3. These include optically-selected SDSS QSOs at 0 < z < 3 (Myers et al, 2006;Ross et al, 2009) Lyman-break galaxies (Adelberger et al, 2005), MIPS 24 µm-selected star-forming galaxies at 0 < z < 1.4 , AGES and DEEP2 red and blue galaxies at 0.25 < z < 1 from the AGES (Hickox et al, 2009;Coil et al, 2008) SDSS-selected luminous red galaxies (LRGs) at 0 < z < 0.7 (Wake et al, 2008), and optically-selected galaxy clusters at 0.1 < z < 0.3 (Estrada et al, 2009). The figure also shows the r 0 for low-redshift galaxies with r-band luminosities in the range 1.5 to 3.5 L , derived from the luminosity dependence of clustering (Zehavi et al, 2011).…”
Section: Clustering Of Dsfgsmentioning
confidence: 99%
“…Taking the square root of the ratios of the autocorrelations yields estimates of the relative bias b rel between red and blue galaxies (e.g., Croton et al 2007;Coil et al 2008;Guo et al 2013;Skibba et al 2014). Constructing the correlation coefficient, r ξ , we find:…”
Section: Introductionmentioning
confidence: 99%